Criminal Conflict Analysis: Factors Causing Criminal Acts in TIPIKOR and TPPUU Cases (Decision Number 06/Pid.Sus-TPK/2022/PN.Bjm) - Syahilla, Vabiola; Widowaty, Yeni (Fakultas Hukum Universitas Muhammadiyah Sorong, 2023)
The compounding of criminal acts of TIPIKOR and TPPU is not a new thing, there are several previous studies that discuss this matter but in mining cases there has been no deeper discussion, this makes the author interested in researching related to the compounding of criminal acts in TIPIKOR and TPPU in the mining sector. This research aims to obtain knowledge related to the factors of concurrent criminal acts in TIPIKOR and TPPU in the mining sector. This research is a normative juridical research. The results of the research are: the factors causing concurrent criminal acts, namely TIPIKOR and TPPU in the mining sector based on the author's analysis in verdict number 06/pid.sus-tpk/2022/pn.bjm, namely the factors of power and opportunity possessed by the perpetrator, which made the perpetrator commit concurrent criminal acts, namely TIPIKOR and TPPU. Keywords: Conjunction of Criminal Acts; TIPIKOR; TPPU.